Typology of digital organizations in the context of digital transformation - M. He (Вестник университета)
The article aims at a conceptual explanation of the components of digital transformation, including such concepts as “digital organization”, “digitization”, “digitalization”, and “digital “destruction”. The reviews of research in the field of digital transformation have shown that there are different explicit definitions of concepts and they are quite heterogeneous. This made it possible to develop definitions of the relevant concepts, resulting in two different conceptual clusters: arbitrary and involuntary concepts. The first cluster covers concepts grouped around the result of a digital organization. The second cluster refers to violations that give rise to a marginal organization. Based on the review of research on digitalization the author presented a typology of digital organizations, which includes four types: analog organization, digital organization of the first, second and third types. The developed typology is a classic version of the typology: two types with minimum and maximum digitalization, which correspond to the end points of this combination. Between them are two more types with a consistently increasing intensity of digitization. It is obvious that the digitalization of organizations begins with the second type, which is characterized by the rapid application of digital technologies and gradually increases to the fourth type, which represents the strategic integration of digital technologies.